The European Union's potential for strategic emissions trading in a post-Kyoto climate agreement - Johan Eyckmans; Cathrine Hagem (Statistics Norway, Research Department, 2008)
The literature suggests that Russia and Ukraine may become large sellers of greenhouse gas emissions permits under the Kyoto Protocol and might exploit their market power to maximize trading profits. The EU countries taken together will probably be net buyers of permits. For any given global target for emission, participation by developing countries with low-cost abatement options would benefit the net buyers of permits because the market price for carbon permits would go down. We explore how the EU could benefit from a broader participation through specific bilateral agreements with developing countries in the post-Kyoto period. The bilateral agreement involves a minimum permit sales requirement which is compensated by a financial transfer from EU to the developing country. Such bilateral agreement enables the EU to act strategically in the permit market on behalf of its member states, although firms in each member state are assumed to be price takers in the permit market. In a numerical simulation we show that an appropriately designed bilateral agreement between the EU and China can cut EU's total compliance cost by one third.
Keywords: D43; Q54; 330; emissions permits; post-Kyoto climate agreement; strategic permit trading